Modeling of viscous flows in two-dimensional turbomachinery cascade via viscous-inviscid interaction method - Mohd Zambri, Yusoff, Dr.; Ibrahim, Hussein, Prof. Dr.; Talal, Yusaf, Dr.; Zulkifli, Ahmad (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/